Our Experience with Arthroscopy of Temporomandibular Joint - Š. Nátek; Z. Jirousek (Česká Stomatologie a Praktické Zubní Lékařství, 2006)
Arthroscopy of temporomandibular joint may be considered as a surgical, minimally invasive diagnostic-therapeutic method, which successfully bridges the gap between the conservative therapy of TMP and a surgical intervention on the open joint. It enables a direct visual evaluation of intraarticular structures of upper articular fissure, position of the disk, and its movements in the liquid medium with possibility of therapeutic intervention. It may be considered as a method of choice in cases, where despite a correct establishment of secondary diagnosis and intensive conservative therapy, there is a further progression of pathological changes and continuing and deteriorating subjective complaints of the patient.The authors describe their own experience with this method. The results of arthroscopic examination in a selected group of patients are described as well as a statistical evaluation of the results of therapy according to the recommendation of the American Association of Oral and Maxillofacial Surgeons (AAOMS). The general successfulness of temporomandibular joint arthroscopy in the selected group of patients was 89.4%. The results of the study are comparable with those of workplaces abroad.